Pengaruh Financial Indicator dan Ukuran Perusahaan Terhadap Kondisi Financial Disstres - Vinah Diyantih; Siti Ruhana Dara (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study aims to determine the effect of financial indicators and company size on the financial condition of the manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange for the period 2014 to 2018. This study uses purposive sampling by using regression logistic analysis to measure financial condition disstres. the results showed that the liquidity ratio and operating capacity did not affect the condition of financial disstres. While the profitability ratio, leverage, and size of the company affect the condition of financial disstres.